Design and implementation of the European‐Mediterranean Postgraduate Programme on Organ Donation and Transplantation (EMPODaT) for Middle East/North Africa countries. (22nd June 2021) - Ballesté, Chloe; Valero, Ricard; Istrate, Melania; Peralta, Particia; Mosharafa, Ashraf Adel; Morsy, Ahmed Ali; Bakr, Mohamed Adel; Kamal Abdelkader, Ahmed Ibrahim; Sheashaa, Hussein; Juvelekian, Georges S.; Khachab, Maha; Ahdab, Reshdi; et al.
Summary: This prospective study reports the design and results obtained after the EMPODaT project implementation. This project was funded by the Tempus programme of the European Commission with the objective to implement a common postgraduate programme on organ donation and transplantation (ODT) in six selected universities from Middle East/North Africa (MENA) countries (Egypt, Lebanon and Morocco). The consortium, coordinated by the University of Barcelona, included universities from Spain, Germany, Sweden and France. The first phase of the project was to perform an analysis of the current situation in the beneficiary countries, including existing training programmes on ODT, Internet connection, digital facilities and competences, training needs, and ODT activity and accreditation requirements. A total of 90 healthcare postgraduate students participated in the 1‐year training programme (30 ECTS academic credits). The methodology was based on e‐learning modules and face‐to‐face courses in English and French. Training activities were evaluated through pre‐ and post‐tests, self‐assessment activities and evaluation charts. Quality was assessed through questionnaires and semi‐structured interviews. The project results on a reproducible and innovative international postgraduate programme, improvement of knowledge, satisfaction of the participants and confirms the need on professionalizing the activity as the cornerstone to ensure organ transplantation self‐sufficiency in MENA countries.